PENENTUAN PRIORITAS PERSPEKTIF BALANCED SCORECARD DENGAN FUZZY ANALYTICAL HIERARCHY PROCESS SEBAGAI BAHAN PERTIMBANGAN KEPUTUSAN: DETERMINING PRIORITIES OF BALANCED SCORECARD PERSPECTIVE USING FUZZY ANALYTICAL HIERARCHY PROCESS AS A DECISION CONSIDERATION - Muhammad Reza Kusuma Wardana; Nina Salsabila Sulistiani; Yuniaristanto (Jurnal Aplikasi Bisnis dan Manajemen (JABM), 2020)
Determining the priority of activities is often seen by the number of people involved in these activities. This occurs because a strategic map has not been prepared based on the priority to perform these activities. The research aims to measure performance and determine priorities from the four perspectives of the Balance Scorecard using the Fuzzy Analytical Hierarchy Process approach. This research took a case study from a newspaper company in Solo. The company's strategic goals were formulated through the Balanced Scorecard including learning and growth, customers, internal business processes and finance perspectives. The weighting of each perspective applied the Fuzzy Analytical Hierarchy Process to obtain perspective priority which can be used as a consideration for the company. The results of this research show that the customer perspective has the highest weight value compared to the other three perspectives, namely 0.611; while the learning and growth perspective has the second highest weight value, which is equal to 0.221. The internal business perspective has a weight value of 0.100, while the financial perspective has the lowest weight value of 0.069. These results show that the customer perspective is a top priority that must be prioritized by the company in designing a strategy map to achieve the company goals. Companies need to design customer-oriented strategies by understanding customer behavior patterns in the future. Keywords: Balanced Scorecard, Fuzzy Analytical Hierarchy Process (FAHP), newspaper industry, performance indicator, priority perspective